KARAKTERISTIK PIPA KALOR DENGAN FLUIDA KERJA ASETON, FILLING RATIO 80 % PADA BERBAGAI KEMIRINGAN - Rahmat Iman Mainil; Ferly Septian Iskandar; Azridjal Aziz (Fakultas Teknik Universitas Riau, 2019)
This paper presents an experimental investigation of thermal characteristics of heat pipe (length of 400 mm and diameter of ¼ ̋) with working fluid aseton. The filling ratio was controlled at 80 %. The effect of heat input and inclination of heat pipe on the thermal characteristics of the heat pipe had been studied with variations of (3-6 W) and (0-90°), respectively. The result showed that the high heat input and inclination resulted to the increase of thermal performance of heat pipe .